Juridical Analysis of Cyberbullying as a Criminal Offense - Samuji (Universitas Muhammadiyah Palu, 2025)
Cyberbullying refers to any actions aimed at hurting or intimidating someone through information technology, particularly the internet. This form of bullying can take various shapes, such as threats, the spread of harmful personal information, or defamation. With the advancement of technology and the increasing accessibility of the internet, cyberbullying has become an increasingly urgent issue to address. Indonesian law covers several aspects related to cyberbullying, but its implementation still faces challenges. This article will analyze the regulations governing cyberbullying, the obstacles encountered in law enforcement, and the legal protection available to victims in Indonesia. The analysis aims to provide a deeper understanding of how Indonesian law addresses cyberbullying as a criminal offense and to strengthen efforts in preventing and combating this issue.